Retrospective study 2005-2015 of all cases of fetal death occurred at ≥23 gestational weeks, in Friusli Venezia Giulia, Italy - Lorenzo Monasta; Manuela Giangreco; Emanuele Ancona; Fabio Barbone; Elisa Bet; Pierino Boschian-Bailo; Giovanna Cacciaguerra; Angelo Cagnacci; Melania Canton; Maddalena Casarotto; Manola Comar; Simona Contardo; et al. (BMC, 2020)
Abstract Background Intrauterine fetal death (IUFD) is a tragic event and, despite efforts to reduce rates, its incidence remains difficult to reduce. The objective of the present study was to examine the etiological factors that contribute to the main causes and conditions associated with IUFD, over an 11-year period in a region of North-East Italy (Friuli Venezia Giulia) for which reliable data in available. Methods Retrospective analysis of all 278 IUFD cases occurred between 2005 and 2015 in pregnancies with gestational age ≥ 23 weeks. Results The incidence of IUFD was 2.8‰ live births. Of these, 30% were small for gestational age (SGA), with immigrant women being significantly over-represented. The share of SGA reached 35% in cases in which a maternal of fetal pathological condition was present, and dropped to 28% in the absence of associated pathology. In 78 pregnancies (28%) no pathology was recorded that could justify IUFD. Of all IUFDs, 11% occurred during labor, and 72% occurred at a gestational age above 30 weeks. Conclusion The percentage of IUFD cases for which no possible cause can be identified is quite high. Only the adoption of evidence-based diagnostic protocols, with integrated immunologic, genetic and pathologic examinations, can help reduce this diagnostic gap, contributing to the prevention of future IUFDs.